Integrative Health through Music Therapy Accompanying the Journey from Illness to Wellness - Hanser, Suzanne B; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
Recent music therapy advances and evidence-based practices have earned respect within the medical sciences and garnered popularity amongst users and practitioners. While integrative medicine treats the whole patient with ayurvedic and allopathic medicine, music therapy provides a safe and effective way of managing stress, pain, unpleasant symptoms, response to illness, and treatment side effects, and has been proven to enhance patients' quality of life and general wellbeing. Exploring the ways in which these methods have been practised throughout history, the author takes readers on a journey from illness to wellness, and shows how this can be guided through music. The book instructs music therapists and other practitioners in the use of specific techniques, providing examples of clinical applications. It includes activities that prepare a music therapist physically, emotionally and musically for this journey with another, and provides case studies to explore the difficulties that might arise. .
Foreword -- Preface -- Introduction. Part I: Maps for the Journey -- 1. In Sickness and in Health -- 2. Integration: Medicine, Health and, Empowerment -- 3. Holistic Healing -- 4. Roots of Healing Music -- Part II: The Journey -- 5. Tuning In: The Music Therapist's Journey -- 6. Stepping into the Journey with your Companion -- 7. Orienting to the Journey: The Mythic Way -- 8. The Journey from Illness to Wellness -- Part III: Pathways through the Journey -- 9. The Way to Comfort -- 10. The Way to Awaken -- 11. The Way to the Musical Self -- The Way to Cope -- Conclusion: The Way to Peace.
Keywords: Applied psychology; Psychotherapy and Counseling